Distribution of aerobic anoxygenic phototrophs in the Eastern Adriatic Sea - Šantić, Danijela; Šestanović, Stefanija; Vrdoljak, Ana; Šolić, Mladen; Kušpilić, Grozdan; Ninčević Gladan, Živana; Koblížek, Michal (Marine environmental research, 2017)
The spatial patterns of aerobic anoxygenic phototrophs abundances were investigated, for the first time, in the Adriatic Sea. Also, the spatial patterns of the whole picoplankton community as well as the environmental factors that potentially influence these patterns were highlighted. AAP abundances was in average 66.9 ± 66.8 × 103 cell mL-1, and their proportion in total bacteria was 7.3 ± 4.3%. These values are in the upper range of AAP abundances observed in marine environments. Multivariate analyses proved that environmental factors influenced the picoplankton community interdependently. Chl a was the main driving factor for the picoplankton community, accounting for 33.3% of picoplankton community variance, followed by NO2- (17.9% of variance explained) and temperature (14.2% of variance explained). Chl a showed stronger correlation with AAPs, non-pigmented bacteria and Picoeucaryotes than with cyanobacteria. Abundance of cyanobacteria was stronger correlated to salinity and the N:P ratio than to nutrient concentrations.
Keywords: salinita; Cyanobacteria; Seawater; Temperature; Water Microbiology; mořská voda; sinice; Salinity; mikrobiologie vody; Adriatic sea; Picoplankton; Aerobic anoxygenic phototrophs; teplota